Energy Storage Applications to Address the Challenges of Solar PV and Wind Penetration in Indonesia: A Preliminary Study - Mukhamad Faeshol Umam; Sesi Selia; Amrullah Farad Sunaryo; Muhammad Rizqi Al Asy’ari (Indonesian Journal of Energy, 2022)
Indonesia intends to increase the renewable energy ratio to at least 23% from the energy mix generated by 2025. This target is also in line with the Paris Agreement that Indonesia ratified in October 2016. However, renewable energy capacity has not been significant, as 11.38% of the total on-grid power capacity (MEMR, 2021). More than 90% of renewable comes from hydropower and geothermal, and only a limited capacity comes from wind and solar energy. On the other hand, wind and solar energy potential are enormous for energy generation in Indonesia. One of the barriers that hinder the use of both is their intermittent nature so that they are not economically profitable and can disrupt the existing power grid. Energy storage systems (ESS) can reduce this intermittent problem as frequency regulators and voltage support to the grid. This paper reviews the potential and challenges of energy storage and renewable power generation, especially wind and solar power. This paper also outlines lessons learned from energy storage systems that have been implemented and are still under development. The discussion focuses on the types of energy storage suitable for applications in Indonesia.